2018
DOI: 10.3928/01484834-20180921-02
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Multiple Attempts on an Admissions Examination to Early Program Performance

Abstract: Background: When a student makes multiple attempts at an admissions assessment, an institution must decide how to incorporate the resulting information into its admissions decision. However, little research exists to guide this decision within a nursing admissions context. Method: This article examines patterns in retesting scores from a nursing admissions assessment and the correlations of four retesting score treatments with scores on an early program assessment. Results: Although test scores do increase wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The preadmission test scores collected during this study did not correlate with grit. Complicating this aspect of the study is the influence of retesting on these preadmission tests to achieve better scores, which many students do (Dunham & MacInnes, 2018). Retaking examinations of this nature could indicate grit (Roszkowski & Spreat, 2016) and student motivation (Dunham & MacInnes, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preadmission test scores collected during this study did not correlate with grit. Complicating this aspect of the study is the influence of retesting on these preadmission tests to achieve better scores, which many students do (Dunham & MacInnes, 2018). Retaking examinations of this nature could indicate grit (Roszkowski & Spreat, 2016) and student motivation (Dunham & MacInnes, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Complicating this aspect of the study is the influence of retesting on these preadmission tests to achieve better scores, which many students do (Dunham & MacInnes, 2018). Retaking examinations of this nature could indicate grit (Roszkowski & Spreat, 2016) and student motivation (Dunham & MacInnes, 2018). In this study, the reported scores for admission into the nursing program were collected without consideration of a retesting effect.…”
Section: Discussionmentioning
confidence: 99%
“…The TEAS, a preadmission test that assesses students' science, reading, and overall preparedness for success in a nursing program. Dunham and MacInnes (2018) reported reliabilities of .92 to .93 for composite scores of the fifth edition TEAS.…”
Section: Data Collectionmentioning
confidence: 99%
“…Many nursing programs require students to achieve benchmarks to be accepted into the program. These benchmarks include a high GPA, either overall or specifically related to the required prerequisite course work, as well as preadmission testing (Dunham & MacInnes, 2018;Olsen, 2017;Robert, 2018;Trofino, 2013;Wambuguh et al, 2016). Throughout the program, nursing students must achieve at least a C or higher to pass a nursing course, have limited opportunities to repeat nursing courses, and may be required to complete a predictor exam prior to graduation (Olsen, 2017;Robert, 2018;Trofino, 2013).…”
Section: Nursing Programsmentioning
confidence: 99%
“…Potential candidates will often withdraw from prerequisite courses if they are not achieving the desired grade, or they may retake required prerequisite courses to earn a higher grade (Schutte, 2016). The same holds for the preadmission exam, which potential candidates will often take several times to meet the benchmark requirements (Dunham & MacInnes, 2018). This study examined for a statistically significant relationship between the repetition of requirements and success or failure on NCLEX-RN.…”
Section: Research Questionsmentioning
confidence: 99%